2013
DOI: 10.1002/jnr.23228
|View full text |Cite
|
Sign up to set email alerts
|

Blocking central galanin receptors attenuates insulin sensitivity in myocytes of diabetic trained rats

Abstract: Galanin (Gal), a bioactive neuropeptide, is widely distributed throughout the central nervous system and has diverse modulatory effects. To understand the central effect of this training-stimulatory peptide on insulin sensitivity, its antagonist M35 was injected into the cerebral ventricle in type 2 diabetic rats. A treadmill running of the rats was used to stimulate circulating Gal secretion and central Gal mRNA expression. The results showed that M35 significantly decreased glucose infusion rates in euglycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…GDM is well established to result in decreased insulin sensitivity, impaired glucose tolerance and subsequently diabetes mellitus. Since galanin was shown to improve glucose tolerance in animals (Bu et al, 2013;He et al, 2011;Liang et al, 2012;Zhang et al, 2012), the observed high values of galanin in GDM subjects may also represent a physiological attempt to restore glucose tolerance, a hypothesis that warrants future investigations. SHBG is a glycoprotein possessing high affinity binding for 17 betahydroxysteriod hormones and involving in transport of sex steroids in plasma (Selby, 1990).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…GDM is well established to result in decreased insulin sensitivity, impaired glucose tolerance and subsequently diabetes mellitus. Since galanin was shown to improve glucose tolerance in animals (Bu et al, 2013;He et al, 2011;Liang et al, 2012;Zhang et al, 2012), the observed high values of galanin in GDM subjects may also represent a physiological attempt to restore glucose tolerance, a hypothesis that warrants future investigations. SHBG is a glycoprotein possessing high affinity binding for 17 betahydroxysteriod hormones and involving in transport of sex steroids in plasma (Selby, 1990).…”
Section: Discussionmentioning
confidence: 86%
“…These data seem to indicate that the higher galanin level may be a consequence of elevated glucose, because higher level of plasma galanin is positively correlated with higher level of blood glucose in the pregnant women with GDM. Administration of galanin antagonist regulated circulating glucose levels by stimulating glucose uptake through the increase of GLUT4 expression and the acceleration of the translocation of GLUT4 to the plasma membrane of various insulin-sensitive cells in animals (Bu et al, 2013;He et al, 2011;Liang et al, 2012;Zhang et al, 2012). Furthermore, coadministration of both galanin and insulin compared with respective treatment with galanin or insulin significantly increased GLUT4 protein levels in myocytes of type 2 diabetic rats (Bu et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, we and others have found that central galanin may facilitate GLUT4 translocation and insulin sensitivity in healthy and type 2 diabetic rats (T2DR) , Liang et al 2012, Bu et al 2013. However, little is known as to whether central alarin is involved in a similar role of ameliorating insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our and other's recent studies demonstrated that administration of M35, a galanin antagonist, reduced 2-deoxy-[3H]-D-glucose (2-DG) content in myocytes and adipocytes as well as glucose infusion rates in the hyperinsulinemic-euglycemic clamp test, which was a direct assessment of insulin sensitivity in healthy and type 2 diabetic rats (Bu et al, 2013;Fang et al, 2014c;Guo et al, 2011;He et al, 2011;Jiang et al, 2009;Liang et al, 2012;. By contrast, our recent study demonstrated that administration of M617, a GalR1 agonist, increased insulin sensitivity in healthy and type 2 diabetic rats (Fang et al, 2014d).…”
Section: Animals Studiesmentioning
confidence: 97%